Moderasi Beragama dan Berbangsa: Pendekatan Kebudayaan dalam Kerja-kerja Moderasi dan Toleransi Wali Songo - Ahmad Baso (Besari)
This article explores the role of Wali Songo in promoting religious moderation and national unity through a cultural approach. As pivotal figures in the spread of Islam in Indonesia, Wali Songo integrated Islamic teachings with local customs, fostering an environment of tolerance and mutual respect among diverse religious communities. By analyzing their strategies and practices, this study highlights how Wali Songo's cultural adaptations not only facilitated the acceptance of Islam but also encouraged harmonious coexistence among different faiths. The findings suggest that the principles of moderation and tolerance championed by Wali Songo remain relevant in addressing contemporary challenges of religious diversity in Indonesia.